Improvement in Ophthalmology knowledge acquisition through a E-learning course - Dukes, Nathan; Poblete Soto, Matías; Rodríguez, Alvaro; Ruz, Cristián; Kunakov, Natasha; Donoso, Rodrigo (Spanish Journal of Medical Education, 2022)
(1) Background: Currently, training in Ophthalmology in Chile is insufficient, though itmay be improved through E-learning. The objective is describing the implementation of anOphthalmology course with e-Learning methodology for medical students and generalpractitioners. Evaluate the perception of the students and the learning results; (2) Methods: For thedesign of the course, the Kern model was used, identifying as the main problem the insufficientophthalmological training of general practitioners in Chile. The evaluation of the student’sperception was carried out in two stages: the first one through a survey at the end of each class,and the second one, at the end of the course for a global analysis. Learning was evaluated through the comparison of results between a multiple-choice test prior to the start of the course as well as afinal test; (3) Results: A course of 33 video-classes grouped in 9 thematic blocks was designed. 2versions were made with 429 students in total. 61% students reported facing ophthalmologicalpathology at least once a week. 78% reported agreeing or completely agreeing that the distancemodality was of their choice. Regarding their self-perception, prior to the course, 22% of thestudents considered that their training in ophthalmology was adequate, compared to 95% of themat the end of the course. Both grades obtained and the percentage of students that approved, had astatistically significant improvement when comparing the results between the diagnostic test andthe final test (5.3: 68.9% vs 6.4: 97.52%, respectively. P <0.001); (4) Conclusions: Ophthalmologycourses in e-learning modality have good satisfaction and allow students to acquire knowledge ofthe specialty.